Efforts to Increase the Activeness of Social Studies Learning in Fourth Grade Through the Short Card Type Active Learning Model - Afni, Wike Dewi Nur; Rezania, Vanda; Fihayati, Zuyyina (MIMBAR PGSD Undiksha, 2024)
In the learning process in Elementary School, the material delivered by the teacher often makes students play a role as recipients of information only, rather than being actively involved in the thinking process. As a result, students are busier taking notes, listening, or answering teacher questions, with little opportunity to actively collect and understand information. This has an impact on the level of student learning activity which is not optimal. This study was conducted to analyze the influence of the level of participation in active learning using the Active Learning Short Card Type model on elementary school students. This study uses the True Experimental method with a Posttest-Only Control Group research design. The population used in this study were grade VI students using simple random sampling. The data collection technique used was a questionnaire distributed to both classes. The data were analyzed using descriptive data analysis techniques and inferential statistical data analysis. The results of the t-test analysis showed that the significance (2-tailed) was 0.000, which means Ho was rejected and Ha was accepted because the significance result was less than 0.005. It can be concluded that there is an influence between the experimental class that applies the Active Learning Short Card Type learning model and the control class that uses the conventional learning model.